2005
DOI: 10.1007/s10902-005-3889-4
|View full text |Cite
|
Sign up to set email alerts
|

Using the Past to Enhance the Present: Boosting Happiness Through Positive Reminiscence

Abstract: cognitive imagery, happiness, memorabilia, positive affect, reminiscence,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
199
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(209 citation statements)
references
References 45 publications
3
199
0
7
Order By: Relevance
“…They report that although narratives strengthen positive emotions in elderly people, emotions created by retelling memories seem to be transient. This method provides a limited insight relative to self and present time and it is the footstone to promote positive emotions and happiness (Bryant, Smart, & King, 2005). Another study investigated the effect of this therapy on depression signs in elderly people, showed that this therapeutic method can be effective (Zadeh, Shahi, & Khani, 2012) that confirms the efficiency of this therapy and complies with the results of this study.…”
Section: Discussionsupporting
confidence: 84%
“…They report that although narratives strengthen positive emotions in elderly people, emotions created by retelling memories seem to be transient. This method provides a limited insight relative to self and present time and it is the footstone to promote positive emotions and happiness (Bryant, Smart, & King, 2005). Another study investigated the effect of this therapy on depression signs in elderly people, showed that this therapeutic method can be effective (Zadeh, Shahi, & Khani, 2012) that confirms the efficiency of this therapy and complies with the results of this study.…”
Section: Discussionsupporting
confidence: 84%
“…This pattern of findings is especially striking in light of the fact that our linguistic analysis revealed that participants in the two savoring conditions did not differ in the frequency of positive emotion words. When people naturalistically savor, they most often choose to savor relational memories (Bryant et al, 2005) and savoring memories not involving other people actually may be a difficult task for some adults. It is unknown whether the types of memories naturalistically savored by adults in LDRs differs from those savored by other adults (single people or GCR members), but it may be that for some adults in LDRs, savoring personal memories fails to enhance emotional state because these memories underscore the fact that they live apart from their romantic partners, which may evoke feelings of longing or being alone.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that people may differ in the extent to which they tend or are able to savor positive experiences, research suggests that strategies to savor can be learned (Bryant et al 2005;Bryant and Veroff 2007), which may probably increase the benefits of vacation as well.…”
Section: The Role Of Vacation Activities and Experiences (Research Qumentioning
confidence: 99%